2009
DOI: 10.1007/s00423-009-0511-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyperparathyroidism–jaw tumor syndrome: a report of three large kindred

Abstract: HPT-JT has a frequent single-gland parathyroid involvement and a relatively increased risk of parathyroid carcinoma. The penetrance of the disease is high but incomplete. Regardless of the denomination of the syndrome, jaw tumors occur rarely, while uterine involvement is frequently present. Selective parathyroidectomy may be an effective strategy, but a prolonged follow-up is required because of the risk of recurrences and malignancies. A systematic investigation is also required because of associated maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 38 publications
2
91
0
7
Order By: Relevance
“…In one study, a mean age at diagnosis of 36 years is reported (17). The median age at diagnosis of HPT was 28.5 years (range in our study; this is in accordance with recently published data (17).…”
Section: Clinical Findingssupporting
confidence: 93%
“…In one study, a mean age at diagnosis of 36 years is reported (17). The median age at diagnosis of HPT was 28.5 years (range in our study; this is in accordance with recently published data (17).…”
Section: Clinical Findingssupporting
confidence: 93%
“…Patients with HPT-JT syndrome have a 15-24% chance of developing parathyroid carcinoma, and loss of heterozygosity of chromosome 1q, the location of the HRPT2/CDC73 gene, is reported to be found in 55% of parathyroid carcinomas. 1,17,[19][20][21] The calcium-sensing receptor (CASR) regulates not only the synthesis and secretion of parathyroid hormone, but also the proliferation of the parathyroid glands. We have previously reported that 31% of parathyroid carcinomas had irregular or absent staining for CASR compared with only 1% of sporadic adenomas.…”
mentioning
confidence: 99%
“…In a Dutch kindred with HPT-JT, Hürtle cell thyroid adenoma was identified [22]. In a large Italian unrelated HPT-JT kindred, thyroid adenoma and PTC were also found [23]. However, association of PTC with HPT-JT has not been determined so far.…”
Section: Discussionmentioning
confidence: 96%